Indigenous system of white-button mushroom production for augmenting farm income in northern India - Shirur, Mahantesh; Manikandan, K; Wakchaure, G C; Mandal, Kunal (Indian Farming, 2018)
Innovation and adoption of various technologies by seasonalmushroom growers of four north Indian states resulted in considerable economic profit to them. It also provided job opportunity for huge number of labourers. These labourers from adjoining states usually migrate during mushroom growing season to Haryana and Punjab to cater the need. In that way, the core labour group refresh their skill of mushroom growing year-after-year, thereby becoming more experienced and the employers get dependable persons to take care of whole activity. The labourers usually work under a leader on contractual basis and relationshipbetween employers and labourers becomes enduring. This ensures smooth running of whole process. Economic returns claimed by farmers are huge, many growers with 60 to 80 huts or above claim to have crossed 1 crore turn over in a season.Hence we may opine that the  seasonal mushroom growing activity by north Indian farmers reached alevel akin to small-scale industry and efforts are needed to replicate this success in other parts of the country with similar climatic conditions and resources. Interpolation of many suchindigenous practices have inherentpotential to bring desirable changes in the lives of rural folk. Detailedeconomic and social impact analysis of such activity needs further investigation and interventions by scientists to further refine the location specific technologies.